Evaluation of the magnitude of hip joint deformation in subjects with avascular necrosis of the hip joint during walking with and without Scottish Rite orthosis. (February 2017) - Karimi, Mohammad Taghi; Mohammadi, Ali; Ebrahimi, Mohammad Hossein; McGarry, Anthony
Highlights: Experimental work via motion analysis system. Using numerical analysis via finite element analysis. Musculoskeletal modeling by the means of CT scan and modeling software. Proposing a new treatment approach for perthes disease. Abstract: The femoral head in subjects with leg calve perthes disease (LCPD) is generally considerably deformed. It is debatable whether this deformation is due to an increase in applied loads, a decrease in bone mineral density or a change in containment of articular surfaces. The aim of this study was to determine the influence of these factors on deformation of the femoral head. Two subjects with LCPD participated in this study. Subject motion and the forces applied on the affected leg were recorded using a motion analysis system ( Qualsis TM ) and a Kistler force plate. OpenSim software was used to determine joint contact force of the hip joint whilst walking with and without a Scottish Rite orthosis. 3D Models of hip joints of both subjects were produced by Mimics software . The deformation of femoral bone was determined by Abaqus . Mean values of the force applied on the leg increased while walking with the orthosis. There was no difference between bone mineral density (BMD) of the femoral bone of normal and LCPD sides ( p -value>0.05) and no difference between hip joint contact force of normal and LCPD sides. Hip joint containment appeared to decrease follow the use of the orthosis. It can be concluded that the deformation of femoral head in LCPD may not be due to change in BMD or applied load. Although the Scottish Rite orthosis is used mostly to increase hip joint containment, it appears to reduce hip joint contact area. It is recommended that a similar study is conducted using a higher number of subjects.